2022
DOI: 10.17072/2079-7877-2022-2-90-108
|View full text |Cite
|
Sign up to set email alerts
|

Geoecology of Thermokarst Lakes of Western Siberia in the Zone of Influence of an Arctic Town (A Case Study of the Town of Nadym)

Abstract: The paper provides geoecological assessment of natural and urban thermokarst lakes for the town of Nadym, typical of the West Siberian Arctic. Although there is no developed industry in the town, we have found that there occurs an anthropogenic transformation of the geochemical composition of the surface waters of urban thermokarst lakes in comparison with background ones, which is manifested in an increase in the alkalinity of water and in chronic contamination with petroleum products. The reasons for these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The business and public area is located in the town center. Gas-fired boilers, a thermal power plant, and vehicles are the main current sources of pollution (Soromotin et al 2022). Previous studies have revealed environmental pollution.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The business and public area is located in the town center. Gas-fired boilers, a thermal power plant, and vehicles are the main current sources of pollution (Soromotin et al 2022). Previous studies have revealed environmental pollution.…”
Section: Study Areamentioning
confidence: 99%
“…Based on Pb and As content, the soils are classified as "unpolluted" and "moderately polluted" (Nizamutdinov et al 2021). Changes in the water composition of urban lakes have also been identified (Soromotin et al 2022).…”
Section: Study Areamentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/w15081577/s1, File S1: Research Methods to Characterize the Chemistry of Thermokarst Lake Water [47][48][49][123][124][125][126][127][128][129]; File S2: Material and Methods of Medical Research [130][131][132][133][134][135][136].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The chemical composition of lakes is also significantly affected by the thawing of organogenic soil horizons [43]. However, the surface waters contain large amounts of Fe, Mn, Cd, Pb, and Cu absorbed by organic components [38,[44][45][46], and in many river sediment samples, high levels of petroleum products, such as Pb, Cr, Zn, Ni, Fe, Mn and Cu (compared to the approved values [47-49]), have also been detected [46]. The trace elements accumulate in the seasonally thawed active layer from thawing snow and melting ice in spring, and they are concentrated in autumn as they are expulsed from the freezing active layer.…”
Section: Introductionmentioning
confidence: 99%